Faktor-Faktor Yang Berhubungan Dengan Perilaku BABS Di Wilayah Kerja Puskesmas Siulak Gedang - Imani, Weci Refira; Nur, Erdi; Awaluddin, Awaludin; Adriyanti, Sri Lestari (Jurusan Kesehatan Lingkungan Poltekkes Kemenkes Padang, 2023)
Open Defecation Free (ODF) is an activity directed at changing the behavior of Open defecationtoward latrines. Based on the data obtained, there are 10 villages with a total of 457 households that have not been verified as open defecation free. The purpose of this study was to determine the factors related to open defecation behavior in the Siulak Gedang Health Center Work Area, Kerinci Regency in 2022. This research was a quantitative study with the approach cross sectional conducted in two villages in the Siulak Gedang Health Center Work Area. . The population in this study were all households in the village with high open defecation status, namely Siulak Gedang Village and Pelak Naneh Village as many as 515 families, with a sample of 100 families. Data was collected through interviews using a questionnaire. Data analysis with univariate and bivariate with statistical chi-square test. The results showed that there was a relationship between knowledge (p = 0.003), attitude (p = 0.000), socioeconomic (p = 0.002), and latrine ownership (p = 0.000) with open defecation behavior. There was no relationship between the support of health workers (p=1) with open defecation behavior. To reduce the number of open defecation (OD), it is hoped that the community always participates in implementing clean and healthy living behaviors, especially in the ownership and use of healthy family latrines.